Moving to Restoration: The Experiences of Women Exiting Sex Trafficking. Issue 1 (2nd January 2019) - Gonzalez, Nicole; Spencer, Chelsea; Stith, Sandra
ABSTRACT: In this article, we use qualitative interviews to learn from three sex-trafficking survivors how service providers can better help female victims of domestic sex trafficking with restoration and recovery, along with how to better identify female victims of sex trafficking and their needs. In this article, participants are referred to as survivors of sex trafficking because they are no longer being trafficked, and individuals who are currently being trafficked are referred to as victims of sex trafficking. Participants reported that therapy, having financial assistance and services provided at no cost, services that focused on rehabilitation to a more independent living and social support were services identified as most helpful for rehabilitation. Participants also discussed barriers to and resources that helped them exit sex trafficking. Implications for future research and for providers are offered.